Deepening Ties but Unfulfilled Hopes: The EFTA Dimension of Western Europe's Relations with Tito's Yugoslavia. Issue 3 (4th May 2022) - Broad, Matthew
Abstract: This article examines the evolution of the European Free Trade Association's (EFTA) relationship with Yugoslavia during the reign of Josip Broz Tito. EFTA has largely been written out of accounts of Western Europe's ties to Belgrade, despite being one of the two principal economic forums on the continent alongside the European Economic Community (EEC). This article, by contrast, posits that the relationship did matter. Notwithstanding its status as an intergovernmental, purely economic free trade bloc, EFTA's attitude was in fact shaped by politico-strategic considerations relating to the Cold War – be it concerns about the independence of Yugoslavia vis-a-vis the Soviet bloc or the prospect that ties with Belgrade might act as a stepping-stone towards East-West détente. The cooperation that emerged should therefore act as a reminder of EFTA's agency during the Cold War and its relevance to post-war European politics. Yet while this relationship pervaded over three decades, its intensity waxed and waned, and EFTA-Yugoslav cooperation often fell short of what both the Yugoslavs and some of EFTA's own members hoped would materialise. As well as tracing the relationship that did develop, therefore, the article also explores why it did not translate into deeper, more meaningful collaboration.